Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Cerita Materi Matriks di SMA N 1 Tondano Berdasarkan Prosedur Newman - Palandeng, Britney Milan; Tumalun, Nicky K.; Wenas, Jhon R. (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2023)
The purpose of this study is to examine the types of errors and the causal factors that were made by students in solving question on matrix based on the Newman procedure. The method of this research is descriptive qualitative. The data was collected by using tests and interviews. The subject of this research is students of class XI IPA 1 at SMA N 1 Tondano. Among these students, Â 6 (six) students were taken as interview subjects. The result of this study is the percentage of studentsâ€™ errors in solving matrix problem which consist: reading error 0.67%, comprehension error 1.33%, transformation error 24%, process skill error and encoding error 37.33%. The factors that cause errors made by students are students: (1) not careful in reading questions and in carrying out matrix addition operation; (2) rushing in solving problems; (3) not understanding the terms of matrix multiplication; (4) not knowing the formula that must be used to solve problem; (5) not making steps to solve problem in detail; (6) incomplete notes; and (7) not learning